Factors Influencing the Saudi Audience, Readers of the Electronic and Printed Newspapers - Abdullah, Louloa Aman Saeed; AlSayed Najidah, Said Abdo; Salem, Duaa Fathi (Journal of Humanities & Social Sciences, 2019)
This study aimed to identify the effective factors on Saudi audience like reading electronic and printed newspaper. The study used the method of media survey in which using in input uses, satisfaction and media richness theory. The study used a questionnaire which applied on sample includes (400) individual.The results of the study indicated that study sample of Saudi audience read Saudi newspapers by 44% (sometimes) and what Saudi audience prefer, electronic newspapers came first by 49. 5%, local topics came first in electronic and printed newspaper, factors affecting in audience reading, the readability of the content to show in large parts came first stage at the electronic newspaper average 3. 91. The ease of using newspaper’s website came at the first order for electronic newspaper average 4. 44. In the light of results, there were a lot of recommendations and proposals to overcome the negative factor which disable audience to read printed and electronic newspapers.In the light of results, several studies were recommended to measure the Saudi audiences’ reading for printed and electronic newspaper in order to monitor audience’s attitudes toward method and the degree of audience’s confidence and to know the impact of social media on both of them and work on putting strategies by press and media institutions to face challenges and threaten its future through working on several discussion meetings with intellectuals , interested and experts in the field of journalism.
Keywords: electronic journalism; print journalism; reading; the Saudi public